The Neo-Weberian State paradigm in the water and sewage sector in Poland - Głuc, Krzysztof (Journal of Public Governance, 2019)
Objectives: The main objective of this article is to investigate the current stage of the public management paradigm in the area of the water and sewage sector in Poland.Research Design & Methods: A thorough examination of the current stage of research of the post-New Public Management concepts is followed by empirical analysis of public management paradigms present in the water and sewage sector in Poland. The research hypothesis focuses on a shift from the NPM model towards other paradigms closer to Neo-Weberian State or a hybrid. Analysis of statistical data is supported by additional arguments related to recent publications and legal changes in the sector.Contribution/Value Added: This article is one of the first analyses of the applications of post-NPM paradigms in the water and sewage sector in Poland. A special emphasis is put on the discussion of NWS elements in the paradigm shift taking place in this sector.Implications/Recommendations: The results of the research conducted prove that the NPM model is still in place in the water and sewage sector in Poland, but gradually, in particular as a result of recent changes to legislation and the introduction of more centralised procedures, the NPM model is being supplemented by new elements that are clearly of a NWS origin. While it is visible that these paradigms co-exist at this point, it is necessary to continue research and thorough observations of the sector to investigate the future development of public management in this area.